In Silico Assessment of the Potential of Patatin as a Precursor of Bioactive Peptides. Issue 3 (2nd December 2015) - Fu, Yu; Wu, Wei; Zhu, Minpeng; Xiao, Zhigang
Abstract: The aim of this study was to evaluate patatin, a major storage protein in potato tuber, as a precursor of bioactive peptides based on in silico approaches. In silico proteolysis of patatin using 16 proteases released numerous bioactive peptides exhibiting antioxidant, angiotensin‐I converting enzyme (ACE) inhibitory, dipeptidyl peptidase (DPP)‐IV inhibitory, glucose uptake, neuropeptide inhibitory and ion flow‐regulating capacities. Chymotrypsin C released the most bioactive sequences from patatin compared with other proteases. In addition, the results of PeptideRanker demonstrated that a number of di‐ and tripeptides derived from patatin possessed great potential as bioactive peptides. Practical Applications: Patatin is a major protein in potato fruit juice, which is regarded as a by‐product of potato starch industry. Effective conversion of patatin into high value‐added ingredients will significantly improve its potential for food application and elevate its commercial value. This study provides a theoretical basis for development of patatin as a high value‐added and biofunctional ingredient in the food industry.